Figurative Language in Billie Ellish’s Songs - Ficky Anis Setiawan; Jonathan Calvin Theodora (English Journal Antartika, 2024)
This research aims to analyze figurative language in song lyrics as a form of emotional expression and personal narrative. The background of this study is based on the global phenomenon of Billie Eilish's popularity as an icon of the younger generation, recognized not only for her innovative music but also for her meaningful lyrics. This research aims to identify, analyze, and explore five figurative languages -metaphors, similes, symbolisms, hyperboles, and personifications- in Billie Eilish's songs, such as Lunch, TV, and Birds of a Feather. The methodology of this study employs a qualitative approach using critical discourse analysis designed to explain and explore the use of figurative language in depth. There are 16 figurative languages in Billie Eilish’s songs divided into five types. The details of those five types are five metaphors, three similes, three symbolisms, three hyperboles, and two personifications. From the result of the research, it can be concluded that figurative language has an important role in Billie Eilish’s song.